2022
DOI: 10.1002/hyp.14485
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical regulations of transpiration and water use strategy in a mature Chinese pine (Pinus tabulaeformis) forest in a semiarid urban environment

Abstract: Urban trees and forests provide multiple ecosystem services for urban dwellers. However, forest water use for these benefits has become one of the critical concerns in dryland regions where water is limited. Negative forest water use impacts could be reduced by selecting tree species with low rates of transpiration. However, the possible changes of urban tree transpiration and its biophysical controls are still unclear. This study monitored the sap flow of a 58‐year‐old Chinese pine (Pinus tabulaeformis) plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Many environmental variables, including soil moisture, soil temperature, air temperature, solar radiation, relative humidity, vapor pressure deficit, and precipitation, help explain the process of plant transpiration [8]. Different studies have indicated that soil moisture plays an important role in transpiration [9][10][11]. Other studies [8,12] have reported that tree transpiration was closely related to changes in solar radiation and vapor pressure Hydrology 2023, 10, 232 2 of 14 deficit.…”
Section: Introductionmentioning
confidence: 99%
“…Many environmental variables, including soil moisture, soil temperature, air temperature, solar radiation, relative humidity, vapor pressure deficit, and precipitation, help explain the process of plant transpiration [8]. Different studies have indicated that soil moisture plays an important role in transpiration [9][10][11]. Other studies [8,12] have reported that tree transpiration was closely related to changes in solar radiation and vapor pressure Hydrology 2023, 10, 232 2 of 14 deficit.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, drought conditions change the water potential at the leaf surface and the atmospheric interface, disrupting water Plant Cell Environ. 2023;46:3218-3228. wileyonlinelibrary.com/journal/pce penetration between the soils and foliar, thus, blocking water transportation from the root to the leaves (Anderegg et al, 2019;Chen, Chen, Xu, et al, 2022). Zhang et al (2022) showed that shallow roots absorb less water when SWC is low, reducing the sap flow (SF).…”
Section: Introductionmentioning
confidence: 99%
“…Drought stress modifies hydraulic characteristics and causes xylem embolism under negative pressure, forming cavitation and duct blockage. Besides, drought conditions change the water potential at the leaf surface and the atmospheric interface, disrupting water penetration between the soils and foliar, thus, blocking water transportation from the root to the leaves (Anderegg et al, 2019; Chen, Chen, & Kong, 2022; Chen, Chen, Xu, et al, 2022). Zhang et al (2022) showed that shallow roots absorb less water when SWC is low, reducing the sap flow (SF).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation